Pengaruh Rendahnya Minat Pemuda Bergabung dalam Organisasi Gerakan Pemuda Ansor di Desa Sukodono Kecamatan Karangrejo Kabupaten Tulungagung - Toriq, Mohammad Zuhril Syichona; Hasib, Mohammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The low interest of youth in organisations can be caused by, among other factors, the internal lack of understanding of the role and benefits of organisations. The main objective of this research is to identify the factors that cause the low interest and analyse its impact on the dynamics and development of the organisation. The methodology used is descriptive qualitative research, with data collection through interviews and documentation. The results show that the low interest of youth is caused by several key factors: personal and psychological dimensions that tend to be individualistic and less comfortable with group social activities; economic and material factors due to the